Tuesday, November 22, 2005

Dinh's 3 Questions

Substitution : x = 4, y = -1, z = -5

I could not do the exponent on the blog so this means exponent ^.

Try to find the answers to the question. Then check your answer that the bottom

1. 3x(3x + 1) -2(2x - 2) =

2. -2y(y + 4) +3y(y + 2) =

3. 2z(1z - 4) +3z(1z + 5) =












1. 3x(3x + 1) -2x(2x - 2) = 2. -2y(y + 4) +3y(y + 2) = 3. 2z(1z - 4) +3z(1z + 5) =
9x^2 + 3x - 4x^2 + 4x = -2y^2 -8y 3y^2 + 5y = 2z^2 - 8z + 3z^2 15z =
5x^2 + 7x = y^2 -3y = 5z^2 + 7z =
5(4)^2 + 7(4) = (-1)^2 - 3(-1) = 5(-5)^2 + 7(-5) =
108 4 90

0 Comments:

Post a Comment

<< Home